The Students' Reading Habit of English Education Study Program at STKIP PGRI Lubuklinggau - Sari, Renita (LP3MKIL, 2021)
This research aimed to identified English reading habits of the sixth semester students of English Education Study Program at STKIP PGRI Lubuklinggau. This research employed in descriptive qualitative research design. The participants were from class B at the sixth semester students of English Education Study Program. The subject was 16 students. The data collected by using questionnaire adapted from a survey of EFL students in Indonesia from Iftanti (2012) and study from Samaranayake (2016) as the instrument to identify about English reading habits at the sixth semester students of English Education Study Program at STKIP PGRI Lubuklinggau. Based on the result of data analysis, the researcher found out the data: 1) 3 motivation English reading habits such as: improved reading skill, to know the knowledge and to improve their vocabularies. 2) Students’ belief, reading English can improve English ability in their activity and 3) Students’ purpose in reading English is for their study. In conlusion, the sixth semester students of English Education Study Program Class B at STKIP PGRI Lubuklinggau have good English reading habits. Students good habits are: they are eager to read English, they spend most of their time reading English texts,and they have strong interest to read English regularly. Key word: Higher Education Students’, Reading, Reading Habit